2010
DOI: 10.3109/15563650903505166
|View full text |Cite
|
Sign up to set email alerts
|

Fatal human poisoning with PadanTM: a cartap-containing pesticide

Abstract: We report a patient who ingested about 13 g of Padan SG, a cartap-containing pesticide. After ingestion, the patient developed multiple seizures and dyspnea and lost consciousness. The patient did not recover and died on the fifth hospital day despite treatment at the early stage of poisoning. The cause of death was multisystem organ failure. Results of toxicological analysis were as follows: concentrations of nereistoxin (cartap metabolite) were 10.6 microg/mL in plasma, 18.2 microg/mL in urine, and 2.6 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…The concentration of Cartap is an important determining factor of the severity of poisoning and outcome [12]. This can be explained from the fact that the maximum quantity of poison ingested in our case was approximately 15-20 mg which is more than the dose reported in Kurisaki et al case and in both cases of Kurisaki et al and Kuwahara et al, gastric lavage was also done early, but their patients died of multiorgan failure [13,14]. Percentage of Cartap in these cases was 75%; in our case all patients had consumed 50% Cartap, probably the most common formulation available, thus justifying the concentration of poison as an important determining factor of mortality.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…The concentration of Cartap is an important determining factor of the severity of poisoning and outcome [12]. This can be explained from the fact that the maximum quantity of poison ingested in our case was approximately 15-20 mg which is more than the dose reported in Kurisaki et al case and in both cases of Kurisaki et al and Kuwahara et al, gastric lavage was also done early, but their patients died of multiorgan failure [13,14]. Percentage of Cartap in these cases was 75%; in our case all patients had consumed 50% Cartap, probably the most common formulation available, thus justifying the concentration of poison as an important determining factor of mortality.…”
Section: Discussionmentioning
confidence: 41%
“…Frequent generalized seizures responded to lorazepam followed by phenytoin sodium and if required levetiracetam. Both Kurisaki et al and Kurisaki reported death of a 36-year-old male and a 50-year-old female, respectively, on the 5 th and 6 th day of ingestion of 75% Cartap [13,14]. In both cases, patient developed MOD (multiorgan failure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cartap is considered to be a low toxicity poison, severe fatalities have been reported. 7 The toxicity of cartap gets enhanced while the patients concomitantly consume foods or drugs of P450 inhibitor. 5 Further the toxicity is enhanced if the amount consumed is more than 75 mL of solution containing 50% cartap along with alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Среди пестицидов, которые могут являться нежелательными примесями в лекарственном растительном сырье, довольно значительное ме-сто занимают средства защиты растений из груп-пы производных нереистоксина [9,10,11].…”
unclassified